An efficient energy lifetime enhancement using node balancing approach - Kocharla, Laxmaiah; Raghava Rao, K (International Journal of Engineering and Technology, 2018)
Wireless sensor network (WSN) is the cutting edge communication entity, which is adopted by various platform such as IoT and other secure wireless area. There are many advantages while dealing with such system which can provide an efficient communication over remove area. Involvement of multiple node in the communication occurred while sending a packet to destination. An efficiency in packet transfer is required which is in terms of shortest path, managing load on each node and finally finding efficiency in data transfer. Balancing the node and its energy is important aspect which help in preventing complete network and make it energy efficient. Previously given solution find its ability in proper communication but lacking in enhancing overall network lifetime. In this paper a mobile threshold energy route optimization using Matrix formulation approach is presented. The Given proposed solution is implemented on Ubuntu Platform using NS2 Simulator. Observed result find enhancement in PDR, Throughput and Less Overhead.